Case study of herbal application (patchai ennai) on diabetic foot ulcer - Anpuchelvi, S.; Sritharan, G. (JUICE, 2016)
In diabetes slight injury to the glucose laden tissue may cause chronic infection and ulcer formation about 15% of all diabetic patients develops foot ulcer in their life time. This herbal application of "Patchai ennai" effectively and completely healed the foot ulcer in 120 days. However further evaluation is required to prove its significance efficacy using with an appropriate evidences on diabetic foot ulcer without lower limb amputation.